Tikkun Olam: Collectivity, Responsibility, History: A Qualitative Study of Tikkun Olam Among Jewish Community Workers in Greater Vancouver - Leslie, Alex (Canadian Social Work Review / Revue canadienne de service social)

(untitled) (Canadian Association for Social Work Education / Association canadienne pour la formation en travail social (CASWE-ACFTS), 2016)
This paper presents findings from qualitative interviews with five Jewish people — two Rabbis and three workers in various community service capacities — about their understandings and practices of the Jewish principle of tikkun olam. Tikkun olam is a Hebrew phrase that means “the repair of the world,” has its roots in Rabbinic law, the Kabbalah and the ‘Aleinu prayer, and became a mainstream term for Jewish social justice work and community contribution in North America following the Shoah (Holocaust). In this study, participants spoke to the imperative to act and responsibility; external tikkun and internal tikkun; collectivity and interconnectedness; the presence of Jewish history in their work, particularly in the case of the Holocaust; and the spiritual dimension of working with people. This study was undertaken with a narrative approach, to honour and preserve understandings of tikkun olam across Jewish communities. This study indicates the continuing influence of tikkun olam in settings both within and outside the Jewish community. Potential future areas of research are the role of spirituality in social workers’ commitment to social justice and the commitment expressed by several participants to work with Aboriginal people based on a shared history of cultural genocide.